THE COMPLEXITY OF THE ITALIAN HEALTHCARE SYSTEM AND ITS RELATIONSHIP WITH CITIZENS AND INSTITUTIONS: WHAT BALANCE IS POSSIBLE? Received: 22nd October 2024 Revised: 28th November 2024, 16th December 2024 Accepted: 6th November 2024 - Milani, Franco; Antonella Eliana Sorgente, (PEOPLE: International Journal of Social Sciences, 2025)
This paper is based on the project work developed by the authors for the executive master's in strategic management and leadership of health organizations, which was attended at the University of Pavia in 2021-2022.The relationship between regulatory and organizational complexity in the healthcare context and the relationship with the patient/citizen is deemed to require i) the implementation of new leadership styles, ii) the dissemination of non-technical skills, iii) the implementation, structured and specific, of participatory processes so that public action is implemented in a tailor-made way for the need of the community for which it was thought, iv) a new mode of communication between stakeholders and institutions so that the ethics of the relationship and communication, transparency, and accountability become the pivot of a new mode of interaction. The project work started by describing the difficulty of managing and interpreting a health context's regulatory and organizational complexity (particularly for hospitals). It then traced a possible mode of interaction between stakeholders and institutions. This article condenses the conclusion of our project work. The content of this article expresses only the views of the authors. None of the opinions can be linked to the organizations the authors work for.